Correction: CDC2 Mediates Progestin Initiated Endometrial Stromal Cell Proliferation: A PR Signaling to Gene Expression Independently of Its Binding to Chromatin. - Griselda Vallejo; Alejandro D La Greca; Inti C Tarifa-Reischle; Ana C Mestre-Citrinovitz; Cecilia Ballaré; Miguel Beato; Patricia Saragüeta (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0097311.].